Keterkaitan Nilai Tekanan Darah dengan Kadar Glukosa Darah Sewaktu dan Kadar Kolesterol pada Kelompok Usia Lanjut - Trisno Putri, Noor Rochmah Ida Ayu; Cahyaningrum, Etika Dewi (Jurnal Gema Keperawatan, 2024)
The elderly or elderly group is very vulnerable to experiencing various health problems. Health problems that are often found in the elderly are related to hypertension, diabetes mellitus and hypercholesterolemia. This is related to a decrease in body resistance due to the aging process experienced. Preventive, curative, promotive and rehabilitative actions by nurses need to be carried out consistently as an effort to prevent complications that can cause depression anddisability in the elderly. The aim of this study was to determine the relationship between elderly blood pressure and instantaneous blood glucose levels and cholesterol levels in the elderly group. This research was an observational study with a cross-sectional design and involved 40 elderly people who visited the elderly posyandu. Observation sheets, sphgnomanometer and GCU meter were used during the data collection process. Data testing uses univariate test analysis to describe the characteristics of the elderly and the chi-square test to show the relationship between variables. The results of the univariate analysis test showed that 80% of the elderly were aged 60 to 74 years, 75% were male, 20% had pre-hypertension, 50% had pre-hypertension, 55% had high blood glucose, and 57,5% had high cholesterol levels. Chi-square analysis showed that there was a correlation between blood pressure values and instant blood glucose levels (p value0,029) and there is no relationship between blood pressure values and cholesterol levels (p value 0,0072). Nurses are expected to continue to improve preventive, curative, promotive and rehabilitative efforts for the elderly to keep them productive and avoid further complications.